The Impact of Applied Linguistics in Enhancing Language Acquisition: Innovative Teaching Strategies to Develop Learners’ Skills - Dr. Musah Issa Zainudeen (Yayasan Mutiara Hati Moeslem, 2026)
This study explores the impact of applied linguistics on enhancing language acquisition among learners, focusing on innovative teaching strategies aimed at developing the four core language skills: listening, speaking, reading, and writing. The research provides a theoretical framework highlighting the role of applied linguistics in improving teaching methods and learning approaches, alongside a review of recent studies in the field. The findings indicate that: incorporating innovative instructional strategies, such as collaborative learning, language simulations, and the use of educational technology, enhances learners engagement and accelerates language acquisition effectively. The study concludes that applied linguistics serves as a fundamental tool for designing advanced educational programs that contribute to the development of learners’ language skills and the achievement of modern language education objectives.